Managing Digital English Education Projects In Uzbekistan: Success Factors And Barriers - Mirzabekova , Sevara (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the management of digital English education projects in Uzbekistan, focusing on the key success factors and barriers influencing their implementation. The study explores how national educational reforms and digital transformation initiatives have created new opportunities for enhancing English language teaching. Using a qualitative research approach, data were collected through document analysis, interviews, and classroom observations. The findings reveal that effective leadership, teacher digital competence, professional development, and stakeholder collaboration significantly contribute to successful project outcomes. At the same time, infrastructural inequalities, inconsistent teacher training, and weak monitoring systems remain major obstacles.